Phonon Transport in Curved Thin Film: Effect of Film Curvature and Radius on Transport Characteristics. Issue 4 (7th June 2017) - Mansoor, Saad B.; Yilbas, Bekir S.
ABSTRACT: Phonon transport inside a curved film is considered and phonon intensity distribution is instigated for various film arc angles and film radii. A thermal disturbance is applied at the edges of the curved film and resulting phonon transport characteristics are simulated by incorporating the radiative phonon transport equation, which is derived for the general coordinate system to fit any film geometry. Equivalent equilibrium temperature is introduced to quantify the phonon intensity distribution inside the film. In the analysis, the total area and the thickness of the film are kept constant for various film arc angles and radii. It is found that equivalent equilibrium temperature decay is sharp in the close region of the high temperature edge inside the curved film. Normalized equivalent equilibrium temperature reduces with increasing arc angle; however, this decrease is not considerable, i.e., it is in order of 4%. Similar arguments are applied for the temperature distribution along the film thickness in the radial direction.